Modulating Popular Culture: Cultural Critics on Tremblay's Les Belles-Soeurs - Martin, Michèle (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2003)
Abstract This paper discusses the appropriation of a work of popular culture as a tactic in a politics of cultural hegemony. The work in question, Michel Tremblay's play Les Belles-Soeurs, is particularly interesting as it is the first working-class cultural production shown in public in the new Québec of the 1960s, where the Quiet Revolution was in full bloom. After sixteen years of conservative government and Church domination in the cultural domain, the province was led by a liberal government whose members were mostly from the urban petty-bourgeoisie. The field of cultural production changed markedly. The study illustrates a project of cultural critique in newspapers with differing audiences. It reveals the tactics adopted to accommodate and recuperate this irruption of popular culture. It compares the treatment of Les Belles-Soeurs by French reviewers in Québec with those in France and with English reviewers in Canada.